Let fnf_{n}fn denote the nthnthnth Fibonacci number. Prove that fn=(n−10)+(n−21)+(n−32)+...+(n−kk−1),f_{n} = \dbinom{n-1}{0}+\dbinom{n-2}{1}+\dbinom{n-3}{2}+...+\dbinom{n-k}{k-1}, fn=(0n−1)+(1n−2)+(2n−3)+...+(k−1n−k), where k=⌊n+12⌋k= \lfloor\frac{n+1}{2}\rfloork=⌊2n+1⌋ Would appreciate if anyone posts a simple and not that long proof for this.
Note by Marc Vince Casimiro 6 years, 6 months ago
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
_italics_
**bold**
__bold__
- bulleted- list
1. numbered2. list
paragraph 1paragraph 2
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
This is a quote
# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"
\(
\)
\[
\]
2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
You can prove this by induction. I'll demonstrate how to show that f10=f9+f8f_{10}=f_9+f_8f10=f9+f8:
f10=(90)+(81)+(72)+(63)+(54)f_{10}=\left(\begin{matrix}9\\0\end{matrix}\right)+\left(\begin{matrix}8\\1\end{matrix}\right)+\left(\begin{matrix}7\\2\end{matrix}\right)+\left(\begin{matrix}6\\3\end{matrix}\right)+\left(\begin{matrix}5\\4\end{matrix}\right)f10=(90)+(81)+(72)+(63)+(54) =(90)+[(70)+(71)]+[(61)+(62)]+[(52)+(53)]+[(43)+(44)]=\left(\begin{matrix}9\\0\end{matrix}\right)+\left[\left(\begin{matrix}7\\0\end{matrix}\right)+\left(\begin{matrix}7\\1\end{matrix}\right)\right]+\left[\left(\begin{matrix}6\\1\end{matrix}\right)+\left(\begin{matrix}6\\2\end{matrix}\right)\right]+\left[\left(\begin{matrix}5\\2\end{matrix}\right)+\left(\begin{matrix}5\\3\end{matrix}\right)\right]+\left[\left(\begin{matrix}4\\3\end{matrix}\right)+\left(\begin{matrix}4\\4\end{matrix}\right)\right]=(90)+[(70)+(71)]+[(61)+(62)]+[(52)+(53)]+[(43)+(44)] =(90)+[(71)+(62)+(53)+(44)]+[(70)+(61)+(52)+(43)]=\left(\begin{matrix}9\\0\end{matrix}\right)+\left[\left(\begin{matrix}7\\1\end{matrix}\right)+\left(\begin{matrix}6\\2\end{matrix}\right)+\left(\begin{matrix}5\\3\end{matrix}\right)+\left(\begin{matrix}4\\4\end{matrix}\right)\right]+\left[\left(\begin{matrix}7\\0\end{matrix}\right)+\left(\begin{matrix}6\\1\end{matrix}\right)+\left(\begin{matrix}5\\2\end{matrix}\right)+\left(\begin{matrix}4\\3\end{matrix}\right)\right]=(90)+[(71)+(62)+(53)+(44)]+[(70)+(61)+(52)+(43)] =[(80)+(71)+(62)+(53)+(44)]+[(70)+(61)+(52)+(43)]=\left[\left(\begin{matrix}8\\0\end{matrix}\right)+\left(\begin{matrix}7\\1\end{matrix}\right)+\left(\begin{matrix}6\\2\end{matrix}\right)+\left(\begin{matrix}5\\3\end{matrix}\right)+\left(\begin{matrix}4\\4\end{matrix}\right)\right]+\left[\left(\begin{matrix}7\\0\end{matrix}\right)+\left(\begin{matrix}6\\1\end{matrix}\right)+\left(\begin{matrix}5\\2\end{matrix}\right)+\left(\begin{matrix}4\\3\end{matrix}\right)\right]=[(80)+(71)+(62)+(53)+(44)]+[(70)+(61)+(52)+(43)] =f9+f8=f_9+f_8=f9+f8
Be careful of odd-even parity when proving it! I used the Recursive Formula of binomial coefficient to prove it.
If I have time I may do the whole proof.
Long Proof: fn=∑k=0n−1(n−1−kk)f_{n}=\displaystyle\sum_{k=0}^{n-1} \binom{n-1-k}{k} fn=k=0∑n−1(kn−1−k) Using Pascal's formula, for each 2≤n2 \leq n2≤n gn−1+gn−2=∑k=0n−2(n−2−kk)+∑j=0n−3(n−3−jj)g_{n-1} + g_{n-2} = \displaystyle\sum_{k=0}^{n-2}\binom{n-2-k}{k}+ \displaystyle\sum_{j=0}^{n-3} \binom{n-3-j}{j}gn−1+gn−2=k=0∑n−2(kn−2−k)+j=0∑n−3(jn−3−j) =(n−20)+∑k=1n−2(n−2−kk)+∑k=1n−2(n−2−kk−1)=\binom{n-2}{0} + \displaystyle\sum_{k=1}^{n-2} \binom{n-2-k}{k} + \displaystyle\sum_{k=1}^{n-2} \binom{n-2-k}{k-1}=(0n−2)+k=1∑n−2(kn−2−k)+k=1∑n−2(k−1n−2−k) =(n−20)+∑k=1n−2((n−2−kk)+(n−2−kk−1))=\binom{n-2}{0}+\displaystyle\sum_{k=1}^{n-2}\left(\binom{n-2-k}{k}+\binom{n-2-k}{k-1}\right)=(0n−2)+k=1∑n−2((kn−2−k)+(k−1n−2−k)) =(n−20)+∑k=1n−2(n−1−kk)=\binom{n-2}{0} + \displaystyle\sum_{k=1}^{n-2}\binom{n-1-k}{k}=(0n−2)+k=1∑n−2(kn−1−k) =(n−20)+∑k=1n−2(n−1−kk)+(0n−1)=\binom{n-2}{0} + \displaystyle\sum_{k=1}^{n-2}\binom{n-1-k}{k} + \binom{0}{n-1}=(0n−2)+k=1∑n−2(kn−1−k)+(n−10) =∑k=0n−1(n−1−kk)=fn=\displaystyle\sum_{k=0}^{n-1}\binom{n-1-k}{k}=f_{n}=k=0∑n−1(kn−1−k)=fn Pretty long and complex. Looking forward to the simple induction @kenny lau :)
Problem Loading...
Note Loading...
Set Loading...
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
You can prove this by induction. I'll demonstrate how to show that f10=f9+f8:
f10=(90)+(81)+(72)+(63)+(54) =(90)+[(70)+(71)]+[(61)+(62)]+[(52)+(53)]+[(43)+(44)] =(90)+[(71)+(62)+(53)+(44)]+[(70)+(61)+(52)+(43)] =[(80)+(71)+(62)+(53)+(44)]+[(70)+(61)+(52)+(43)] =f9+f8
Be careful of odd-even parity when proving it! I used the Recursive Formula of binomial coefficient to prove it.
If I have time I may do the whole proof.
Long Proof: fn=k=0∑n−1(kn−1−k) Using Pascal's formula, for each 2≤n gn−1+gn−2=k=0∑n−2(kn−2−k)+j=0∑n−3(jn−3−j) =(0n−2)+k=1∑n−2(kn−2−k)+k=1∑n−2(k−1n−2−k) =(0n−2)+k=1∑n−2((kn−2−k)+(k−1n−2−k)) =(0n−2)+k=1∑n−2(kn−1−k) =(0n−2)+k=1∑n−2(kn−1−k)+(n−10) =k=0∑n−1(kn−1−k)=fn Pretty long and complex. Looking forward to the simple induction @kenny lau :)